Analysis of clinicopathological features of the echinoderm microtubule‐associated protein‐like‐4‐anaplastic lymphoma kinase fusion gene in Chinese patients with advanced non‐small‐cell lung cancer. Issue 3 (May 2014) - Liu, Yu‐Tao; Shi, Yuan‐Kai; Hao, Xue‐Zhi; Wang, Lin; Li, Jun‐Ling; Han, Xiao‐Hong; Li, Dan; Zhou, Yu‐Jie; Tang, Le
Abstract Background The echinoderm microtubule‐associated protein‐like‐4‐anaplastic lymphoma kinase (EML4‐ALK) fusion gene defines a novel molecular subset of non‐small‐cell lung cancer (NSCLC). However, the clinicopathological features of patients with the EML4‐ALK fusion gene have not been defined completely. Methods Clinicopathological data of 200 Chinese patients with advanced NSCLC were analyzed retrospectively to explore their possible correlations with EML4‐ALK fusions. Results The EML4‐ALK fusion gene was detected in 56 (28.0%) of the 200 NSCLC patients, and undetected in 22 (11.0%) patients because of an insufficient amount of pathological tissue. The median age of the patients with positive and negative EML4‐ALK was 48 and 55 years, respectively. Patients with the EML4‐ALK fusion gene were significantly younger (P < 0.001). The detection rate of the EML4‐ALK fusion gene in patients who received primary tumor or metastatic lymph node resection was significantly higher than in patients who received fine‐needle biopsy (P = 0.003). The detection rate of the EML4‐ALK fusion gene in patients with a time lag from obtainment of the pathological tissue to EML4‐ALK fusion gene detection ≤48 months was significantly higher than in patients >48 months (P = 0.020). The occurrence of the EML4‐ALK fusion gene in patients with wild‐type epidermal growth factor receptor (EGFR) was significantly higher than in patients with mutant‐type EGFR (42.5% [37/87] vs. 6.3% [1/16], P = 0.005). Conclusions Younger age and wild‐type EGFR were identified as clinicopathological characteristics of patients with advanced NSCLC who harbored the EML4‐ALK fusion gene. The optimal time lag from the obtainment of the pathological tissue to the time of EML4‐ALK fusion gene detection is ≤48 months.